Representasi Keserakahan Manusia dalam Film “The Lorax” Perspektif Eco-Theology - Mohamad Fikri Maulana; Muhammad Galuh Dzikrillah; Naira Rizkia Putri; Qirsa Arifa Fitriyani; Dadan Firdaus (Indo Publishing, 2026)
This study was conducted in response to the growing environmental problems largely caused by excessive human exploitation of nature. The Lorax (2012) was selected as the object of analysis because it presents a clear depiction of how environmental destruction affects the sustainability of life. The purpose of this study is to explore the representation of environmental degradation in the film through the perspective of Islamic eco-theology. This research employs a qualitative method using a library research approach. Data were collected through observations of the film and supported by books, journal articles, and previous studies related to environmental issues and eco-theology. The collected data were analyzed using textual analysis and a phenomenological hermeneutic approach. The findings reveal that The Lorax portrays several forms of environmental degradation, including deforestation, habitat loss, air and water pollution, and ecological imbalance. The character of Once-ler represents human greed that prioritizes economic interests over environmental sustainability. From the perspective of Islamic eco-theology, such behavior contradicts the role of humans as khalifah (stewards of the Earth), who are entrusted with the responsibility of protecting and preserving nature. The film also suggests that environmental crises are not merely ecological issues but are closely connected to moral and spiritual awareness. Through the character of the Lorax and Ted’s effort to replant the last Truffula seed, the film conveys a message of hope that environmental restoration is possible when people are willing to care for and reconnect with nature.